2005
DOI: 10.1111/j.1742-7843.2005.pto_116.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular Effects of Histaminergic Agents on Morphine‐Induced Anxiolysis in the Elevated Plus‐Maze in Rats

Abstract: Some reports indicate that morphine can induce anxiolytic effects both in animal and in man. It has also been reported that histaminergic system can interfere with some pharmacological effects of morphine. The effects of histaminergic agents on morphine-induced anxiolysis in rats, using elevated plus-maze were investigated in the present study. Intraperitoneal injection of morphine (3, 6 and 9 mg/kg) induced antianxiety effects. Intracerebroventricular administration of histamine at the doses of (5, 10 and 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 25 publications
2
25
1
Order By: Relevance
“…In fact, morphine has already been shown to decrease fear-and anxiety-related behaviors in rhesus monkeys [59] and in humans [60]. Furthermore, injection of morphine in healthy rats either has no effect [26] or induces anxiolytic effects [61,62] when tested in the EPM. Part of the explanation for this divergence in morphine effectiveness in relieving anxiety could involve the anxiety-like behavioral test employed, the dose used, the route of administration (systemic vs central vs local injection) and the injection protocol (acute vs sustained).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, morphine has already been shown to decrease fear-and anxiety-related behaviors in rhesus monkeys [59] and in humans [60]. Furthermore, injection of morphine in healthy rats either has no effect [26] or induces anxiolytic effects [61,62] when tested in the EPM. Part of the explanation for this divergence in morphine effectiveness in relieving anxiety could involve the anxiety-like behavioral test employed, the dose used, the route of administration (systemic vs central vs local injection) and the injection protocol (acute vs sustained).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that experimental anxiety can be achieved by coadministration of a neuronal histamine releaser (thioperamide) with a histamine agonist (betahistine) [32] . The anxiogenic effect of histamine and related compounds has also been reported following injection into some brain regions, such as the nucleus basalis magnocellularis [14] , nucleus accumbens [33] , inferior colliculus, periaqueductal gray [34] , cerebroventricle [35] and ventral hippocampus [36] . We also reported an anxiogenic effect following injection of histamine into the central nucleus of the amygdala in our previous study [37] .…”
Section: Discussionmentioning
confidence: 99%
“…First, opiods are clinically known for their potent analgesic action, but they can also cause deep depression of the CNS and potentiate the sedative-hypnotic effects of benzodiazepines [11]. Moreover, preclinical evaluation of morphine has shown that this opioid agonist can induce anxiolysis after both peripheral and central administration [12,13]. Second, it is well accepted that the opioid endogenous system plays a role in the anxiolytic action of benzodiazepines.…”
Section: Introductionmentioning
confidence: 99%